Group Oral Policy Analysis Presentation - Hobbs, Annaleigh; Roggenkamp, Suzanne; Tonjes, Jade (Kansas State University. K-State Libraries, 2022)
For this project, the main goal was to analyze one specific expenditure or tax policy from a nonpartisan position and then present it to the class. The oral presentation was required to be 10 minutes long with a visual and citations to back up the claims. Since it is nonpartisan, we were not allowed to sway our audience to think one way or another about the issue. Rather, we were to recite a plethora of research about the topic. After presenting, every group would be asked a number of questions about their research, such as research methods used or how systems work. Within the project, we were asked to cover topics such as economic theory, costs, benefits, published economic research about the topic, and how the policy works. We were required to have at least 10 sources used in the project, but it was recommended that you utilized more. We then had 1 and a half months to work on our projects.
Kirmser Undergraduate Research Award - Group category, honorable mention
Keywords: Nonpartisan; Economic theory; Cost-Benefit Analysis; Parental Leave; Policy Makers